Modeling and simulation of DC and microwave characteristics of AlInN(AlGaN)/AlN/GaN MOSHEMTs with different gate lengths. (31st May 2018) - Amarnath, G.; Panda, D.K.; Lenka, T.R.
Abstract: In this paper, direct current (DC) and microwave characteristics are modeled and analyzed for AlInN(AlGaN)/AlN/GaN metal‐oxide‐semiconductor high electron mobility transistors with different gate lengths. The 2‐dimensional electron gas sheet charge density ( n s ) model is developed by considering polarization effect and flat‐band voltage with lowest occupied energy level ( E 0 ) in the quantum well. The drain current, transconductance, and gate charge model is developed by incorporating approximation of n s as proposed in this paper. Then, the cut‐off frequency is calculated from the transconductance and gate capacitance model. The analytical model results are in good agreement with Technology Computer Aided Design simulation and experimental results from literatures for DC and microwave characteristics for the proposed gate lengths (0.1, 0.2, and 0.3 μm). From these characteristics, it is also observed that AlInN/AlN/GaN MOSHEMT shows superior DC and radio frequency performance as compared with AlGaN/AlN/GaN MOSHEMT. AlInN/AlN/GaN MOSHEMT produces high drain current (2.34 A/mm) and high cut‐off frequency (124 GHz) at smaller gate length.